Chronic Hypertension in Pregnancy: New Concepts for Classification and Management - Chahine, Khalil M.; Sibai, Baha M. (American Journal of Perinatology, 2019)
Chronic hypertension in pregnancy is traditionally classified according to degree of blood pressure (BP) elevation. Alternatively, stratifying women as high or low risk based on the etiology of hypertension, baseline work-up, and comorbid medical conditions will better inform clinicians about thresholds to initiate antihypertensive therapy, target BPs, frequency of antepartum visits, and timing of delivery. Women classified as high-risk chronic hypertension as described here require stricter BP management and more frequent follow-up visits as their associated rates of adverse maternal and/or fetal/neonatal outcomes appear higher than women classified as low-risk chronic hypertension. The latter group can in most cases be managed similarly to the general obstetric population.
Keywords: chronic hypertension in pregnancy; high-risk chronic hypertension; low-risk chronic hypertension; management of chronic hypertension; classification; chronic hypertension